Switzerland : Financial Sector Assessment Program; Factual Update; IOSCO Objectives and Principles of Securities Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper presents a factual update of the International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation for Switzerland. Overall, there has been substantial progress in implementing Financial Sector Assessment Program recommendations in various areas of securities regulation. In part, changes have been motivated by the need to adapt securities regulations in Switzerland to international developments. The project to unify financial supervision under the Federal Authority for Market Oversight is expected to strengthen the budgetary independence, staffing, and enforcement powers of the supervisor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet